Preconceptional and prenatal exposure to diurnal temperature variation increases the risk of childhood pneumonia - Xiangrong Zheng; Jian Kuang; Chan Lu; Qihong Deng; Haiyu Wu; Rachael Gakii Murithi; McSherry Brownel Johnson; Wang Peng; Maolan Wu (BMC, 2021)
Abstract Background Pneumonia is the leading cause of death and hospitalization among young children worldwide, but its risk factors remain unclear. Objective To evaluate the effect of maternal exposure to diurnal temperature variation (DTV) during preconceptional and prenatal periods on childhood pneumonia. Methods A retrospective cohort study by case-control design was conducted for pneumonia (N = 699) and normal (N = 811) children under age of 14 who were enrolled in XiangYa Hospital, Changsha, China from May 2017 to April 2019. Demographic data including gender, age, birth season, gestational age, parity, mode of delivery, and parental atopy were collected from the electronic medical records in the hospital system. We obtained the data of daily DTV in Changsha during 2003-2019 from China Meteorological Administration. Maternal exposure to DTV during preconceptional and prenatal periods was respectively calculated by the average of daily DTV during one year and three months before conception and entire pregnancy as well as the three trimesters. The association between maternal exposure to outdoor DTV and childhood pneumonia was analyzed by multiple logic regression model. Results We found that childhood pneumonia was significantly associated with exposure to an increase in DTV during one year before conception and entire pregnancy, with ORs (95 % CI) = 2.53 (1.56-4.10) and 1.85 (1.24-2.76). We further identified a significant risk of pneumonia of DTV exposure during the first and second trimester of pregnancy. Sensitivity analysis showed that boys were more susceptible to the effect of prenatal exposure to outdoor DTV during pregnancy particularly in the first two trimesters compared to girls. Conclusions Preconceptional and prenatal exposure to DTV plays an important role in development of childhood pneumonia, especially during the first and second trimesters of pregnancy.